The only common factor of those two terms is the number three, giving you: 3(x3 - 8y3)
2 to the 2 power = 4 -3 to the 2 power = 9 4 to the 2 power = 16 You don't indicate what to do to the 4, but 9 + 16 = 25
2
It is: 2 to the power 4 times 7 to the power 2 = 784
2 to the power of 4 is an expression, it is not an equation.
It is: (-3x-4)(x+2) when factored
2x 2x to the second
The only common factor of those two terms is the number three, giving you: 3(x3 - 8y3)
2 to the 2 power = 4 -3 to the 2 power = 9 4 to the 2 power = 16 You don't indicate what to do to the 4, but 9 + 16 = 25
2
It is: 2 to the power 4 times 7 to the power 2 = 784
2 to the power of 4 is an expression, it is not an equation.
The value of 4 to the power of -2 is 0.0625
4
It would be 4 because 2 to the second power is really 2 * 2, which equals 4.
2 root 4 = 2 x 2; -2 to the power 4 is 16 (-2/4/-8/16)
They are equal 2^4 and 4^2 both equal 16.